RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES WITH THE BEHAVIOR OF TBC SUFFERERS IN THE HEALING PHASE AT THE DOTS CLINIC, RS X - Yulyanti Putri Pratiwi; Indriati Kusumaningsih; Paramitha W. N. M (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
Background: Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis. This study aims to determine the relationship between knowledge and attitudes with the behavior of TB sufferers in the healing phase at the DOTS clinik, RSCK Tzu Chi. Methods: This study was a descriptive correlative study using cross sectional approach. The sample of this research is the TB sufferers who seek treatment at the DOTS clinic of RSCK Tzu Chi with 75 respondents. Sampling method used was questionnaire, univariate analysis in the form of frequency distribution and bivariate analysis used Chi-Square test. With significance p value <0,05. Results: The result of this study showed that there was no significant relationship between knowledge (p 0,051) presentage good knowledge responden 66.7% ,and attitudes (p 0,152) with behavior of TB sufferer, presentage good attitude responden 69.3%. Conclusion: The advice given is to be a positive input and can provide counseling to TB sufferers that are held once a month, in order to increase understanding of TB patients.